simplify (2x-3) (5x^2-6x+9)-3x(5x^2+9)
Answers
Answered by
0
First take the first two brackets and solve
(2x-3)(5x^2-6x+9)
=10x^3 - 12x^2 + 18x - 15x^2 - 18x + 27
= 10x^3 -27x^2 + 27
Now take the last bracket
-3x (5x^2 + 9)
= -15x^3 - 27x
Now take both sides
10x^3 - 27x^2 + 27 - 15x^3 - 27
= -5x^3 - 27x^2
Ans : -5x^3 - 27x^2
Hope it helps!
-ArjunIsCool
(2x-3)(5x^2-6x+9)
=10x^3 - 12x^2 + 18x - 15x^2 - 18x + 27
= 10x^3 -27x^2 + 27
Now take the last bracket
-3x (5x^2 + 9)
= -15x^3 - 27x
Now take both sides
10x^3 - 27x^2 + 27 - 15x^3 - 27
= -5x^3 - 27x^2
Ans : -5x^3 - 27x^2
Hope it helps!
-ArjunIsCool
Rashmi7545:
dekho accha sai -3xinto+9 is -18 hota hai ok
Answered by
0
Isme 2nd last line me - 27ki jagah +27hoga... And last mei 26ki jagah 68 hoga....
Attachments:
![](https://hi-static.z-dn.net/files/d04/4460d8bd1485846c20e04b544c5e2e58.jpg)
Similar questions